Biosorben Daun Ketapang dengan Pengaktifan Asam Sitrat sebagai Pereduksi Merkuri - Yuli Ristianingsih; Muhammad Aulia Fadhil; Fariz Maulana Akbar; Annissa Millenia Ramadhani; Isna Syauqiah (Jurnal Teknologi Agro-Industri, 2019)
South Kalimantan has a gold mining industry that produces waste that can pollute the environment and is harmful to public health. One of the hazardous contaminants contained in the gold mining industry is mercury. This study aims to make biosorbent of ketapang leaves which will be used to reduce mercury content in gold mining waste.. The study began with washing the ketapang leaves to remove the impurities and then dried 3-4 days under the sun to reduce the water content. The next step is a simple carbonization process by using furnaces at a temperature of 300 oC for 30 minutes as the optimum operating condition so that activated carbon is formed called BDK. In the final stage, the biosorbent of ketapang leaves with 0.1 N citric acid was activated to produce biosorbent of ketapang leaves called BDK-COOH. The test results were carried out by SEM and FTIR analysis. The results of SEM analysis showed biosorbents that form large and large pores caused by carbonization and activation processes. Likewise, the results of FTIR analysis formed an active functional group to absorb heavy metals in terms of shifting absorption bands shown by FTIR. However, the adsorption capacity of biosorbent has not been determined so that further research is needed to find out.